Evaluation of probiotic properties and complete genome analysis of lactic acid bacteria isolated from crested ibis Nipponia nippon feces - Yang, Lei; Luo, Jie; Zeng, Yan; Zhang, Baoyue; Wang, Yang; Shu, Gang; Zhao, Xiaoling; Lin, Juchun; Li, Haohuan; Xu, Funeng; Zhang, Wei; Fu, Hualin; et al. (Frontiers in Microbiology, 2025)
IntroductionCrested ibis (Nipponia nippon) is a rare bird whose intestinal tract is rich in lactic acid bacteria (LAB), but there is less research on LAB isolated from crested ibises.MethodsFrom the fecal samples, Twenty isolates were obtained from fecal samples and subjected to a series of tests, including biochemical identification, acid and bile tolerance assays, in vitro pathogen inhibition, cell surface hydrophobicity assessment, antibiotic susceptibility testing, and hemolytic activity evaluation to determine their probiotic potential. We fed L. plantarum E7 to mice to evaluate safety. Nanopore PromethION48 and the Illumina Novaseq sequencing platforms were used to sequence the genome of L. plantarum E7.ResultsFive isolates (D1, D2, D6, E7 and D8) were able to survive under low acid and high bile salt conditions. Except for D8, the other four isolates (D1, D2, D6 and E7) exhibited inhibitory activity against tested pathogens. Strain E7 displayed the least resistance to antibiotics, and only E7 showed medium hydrophobicity. Further characterization identified strain E7 as Lactiplantibacillus plantarum (L. plantarum) through 16S rDNA sequencing. We did not observe adverse effects of L. plantarum E7 on growth performance, blood cell composition in mice. L. plantarum E7 consists of a circular chromosome and two circular plasmids. The chromosome encodes 3024 genes that associated with cell adhesion, acid and bile salt tolerance, antioxidant enzymes, as well as the production of secondary metabolites. In contrast, the plasmids contain fewer coding genes. Functional annotation via KEGG and GO database analysis indicated that the genes of L. plantarum E7 are primarily involved in carbohydrate metabolism, amino acid metabolism, vitamin and cofactor metabolism, biological process, and molecular function.ConclusionThis study provides a theoretical foundation for developing new probiotic for crested ibises.